Chemical characterization of Plukenetia volubilis (Sacha inchi) cake cultivated in Cuba. Technical note - Scull, Idania; García, Yaneisy; Ortega, Dania; Albelo, Nereida; Sosa, Dailyn; Valiño, Elaine C.; García, Yanelys (Cuban Journal of Agricultural Science, 2022)
The Plukenetia volubilis (Sacha inchi) cake cultivated in Cuba was chemically characterized. In order to evaluate the nutritive composition crude protein, ash, fiber fractionation, and mineral composition (macronutrients) were determined. The qualitative assay of the phytochemical sieve was used to study the secondary metabolites of the sample. The results showed high CP (54.41 %) content while the values of neutral detergent fiber, acid detergent fiber, lignin and cellulose were low (30.97, 11.84, 3.54, respectively, and 8.04 % of dry matter), if they are compared with cakes from other oleaginous plants. The majority functional groups corresponded to terpenes and α amine. The alkaloids were howed in a moderate way and, to a lesser extent, flavonoids and tannins. The Sacha inchi cake cultivated in Cuba has high crude protein values, moderate fibrous components content, adequate ash evels and phytocompounds, which confirm their potentialities as an alternative food source. Key words: alternative protein, nutritional composition, minerals, secondary compounds